Prospection of putative genes for digestive enzymes based on functional genome of the hepatopancreas of Amazon river prawn - Rocha, Cássia Pantoja; Maciel, Carlos Murilo Tenório; Valenti, Wagner C. [UNESP]; Moraes-Valenti, Patricia [UNESP]; Sampaio, Iracilda; Maciel, Cristiana Ramalho (Universidade Estadual de Maringa, 2022)
Over recent years, Macrobrachium amazonicum has become a popular species for shrimp farming due to their fast growth, high survival rates, and marketability. Several studies have focused on the development of new technology for the culture of this species, but many aspects of their nutrition and physiology remain unknown. Thus, the goal of the present study was to obtain transcripts of putative genes encoding digestive enzymes, based on a library of the cDNA from the hepatopancreas of M. amazonicum, sequenced in the Ion Torrent™ platform. We identified fragments of nine genes related to digestive enzymes, acting over proteins, carbohydrates and lipids. Endo and exoproteases were also recorded in the hepatopancreas, indicating adaptation to the digestion of protein-rich foods. Nonetheless, the enzymes involved in the carbohydrate metabolism formed the largest functional group in M. amazonicum, including enzymes related to the digestion of starch, chitin, and cellulose. These findings indicate that the species has a genetic apparatus of a well-adapted omnivorous animal. This information may provide important insights for the selection of ingredients for the formulation of a more appropriate diet to the enzymatic repertoire of M. amazonicum.
Keywords: Amylase; Cathepsin; Cellulase; Transcriptome; Trypsin